AGEP overlap induced by hydroxychloroquine: a case report and literature review. Issue 6 (2nd November 2018) - Mercogliano, Christopher; Khan, Muhammad; Lin, Catherine; Mohanty, Elan; Zimmerman, Ryan
ABSTRACT: Acute Generalized Exanthematous Pustulosis (AGEP) is a rare drug reaction manifesting as pustular lesions with surrounding erythema following exposure. The disease is often self-limited and treatment is supportive. It may present in an atypical variant with vesicles that desquamate into erosions, which classifies the disease as an AGEP/SJS Overlap. This overlap syndrome can carry a substantial mortality rate and necessitate elevation in the level of care. Hydroxychloroquine has been implicated in cases of AGEP, and we present a case of AGEP/SJS overlap attributed to this common medication. Given the prevalence of drug eruptions, it is critical for the physicians to recognize and not overlook this rare and potentially fatal dermatological emergency.